Has the link between the spot and forward exchange rates broken down? Evidence from rolling cointegration tests - Ali M. Kutan; Su Zhou (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
In a recent survey, Engel (1996) reported conflicting results about the cointegration relationship between the spot and forward exchange rates. Applying rolling cointegration tests to the mark, yen, and Swiss franc with respect to the U.S. dollar for the post-80 period, we find that the relationship between the two rates broke down in the late 1980s. Although they became cointegrated again during the mid-90s, they no longer co-moved proportionally, however. It is argued that failure to account for such significant structural changes in the data generating process may explain the conflicting findings in the literature.
Keywords: 330; Devisentermingeschäft; Wechselkurs; US-Dollar; Schätzung; Deutschland; Japan